Isolation, analytical measurements, and cell line studies of the iron–bryostatin-1 complex. Issue 10 (15th May 2016) - Plummer, Sydney; Manning, Thomas; Baker, Tess; McGreggor, Tysheon; Patel, Mehulkumar; Wylie, Greg; Phillips, Dennis
Graphical abstract: Bryostatin-1 is a marine natural product that has demonstrated medicinal activity in pre-clinical and clinical trials for the treatment of cancer, Alzheimer's disease, effects of stroke, and HIV. In this study, iron–bryostatin-1 was obtained using a pharmaceutical aquaculture technique developed by our lab that cultivates marine bacteria for marine natural product extraction. Analytical measurements 1 H and 13 C NMR, mass spectrometry, and flame atomic absorption were utilized to confirm the presence of an iron–bryostatin-1 complex. The iron–bryostatin-1 complex produced was then tested against the National Cancer Institute's 60 cell line panel. Adding iron to bryostatin-1 lowered the anti-cancer efficacy of the compound. Abstract: Bryostatin-1 is a marine natural product that has demonstrated medicinal activity in pre-clinical and clinical trials for the treatment of cancer, Alzheimer's disease, effects of stroke, and HIV. In this study, iron–bryostatin-1 was obtained using a pharmaceutical aquaculture technique developed by our lab that cultivates marine bacteria for marine natural product extraction. Analytical measurements 1 H and 13 C NMR, mass spectrometry, and flame atomic absorption were utilized to confirm the presence of an iron–bryostatin-1 complex. The iron–bryostatin-1 complex produced was then tested against the National Cancer Institute's 60 cell line panel. Adding iron to bryostatin-1 lowered the anti-cancer efficacy of the compound.